A Flexible Smart Monitoring System for the Conservation of Textile Relics. (6th August 2021) - Lin, He; Yao, Meiyu; Tao, Yifei; Li, Guangzhe; An, Liang; Li, Li
Abstract: Textiles and apparel archaeology is an indispensable part of history and archaeology. As most unearthed textile relics are silk, soft and multi‐layered in nature, their frangibility poses enormous difficulties in their transportation, storage and exhibition. Traditional methods may not be suitable for accurately monitoring their condition under various external situations, due to the particularity of the textile relics. Herein, a smart, flexible, fabric‐based monitoring system, which integrates sensing fibers, textile technology, and traditional silkscreen conservation, is developed for the preservation and conservation of textile relics. The proposed integrated electrochemical fabric bears a high level of flexibility and diversification in structure, and furthermore can act as a protective cover to monitor external environmental impact factors such as pH value, strain, humidity, temperature, and ultraviolet light. The newly developed system can act as a daily monitoring solution to achieve real‐time and prolonged preventative control from various mechanisms of degradation, so as to ultimately support and uphold the conversation and preservation of textile relics. Abstract : An innovative textile‐based monitoring system, which is formed by weaving pH, strain, humidity, temperature and UV light sensing fibers into an electrochemical fabric, is proposed to provide a reliable and integrated solution for the conservation of textile relics using integrated cultural preservation and smart textile technology.